Treatment Patterns and Survival Outcomes of Non-Small Cell Lung Cancer Patients Initially Diagnosed With Brain Metastases in Real-World Clinical Practice - Chen, Xin-Ru; Hou, Xue; Dinglin, Xiao-Xiao; Liu, Yong-Dong; Li, Yin; Zheng, Wei; Li, De-Lan; Chen, Jing; Wu, Xiao-Liang; Wang, Kai-Cheng; Ma, Shu-Xiang; Zeng, Yin-Duo; et al. (Frontiers in Oncology, 2020)
Background: This study aimed to comprehensively analyze the characteristics, treatment patterns and survival outcomes of non-small-cell lung cancer (NSCLC) patients initially diagnosed with brain metastases (BMs) in real-world practice. Methods: We enrolled NSCLC patients initially diagnosed with BMs between Jan 2004 and Jan 2018 in our institution. Patient demographics, treatment modalities and survival outcomes were then analyzed. Brain localized treatment (BLT) included early brain radiotherapy (EBR), deferred brain radiotherapy (DBR) and surgery. Results: A total of 954 patients were identified. Concerning initial treatment, 525 patients (55.0%) received systemic medication (SM)+BLT, 400 patients (41.9%) received SM only, and 29 patients received BLT only (3.0%). SM+BLT cohort was associated with longer median overall survival (mOS) than the SM only and the BLT only cohorts both in epidermal growth factor receptor (EGFR)/anaplastic lymphoma kinase (ALK)-negative/unknown patients (15.3 months, 95% confidence interval [CI], 14.2-16.4; 11.1 months, 9.0-13.2; 7.0 months, 5.4-8.6; p<0.001) and in EGFR/ALK-positive patients (33.7 months, 28.5-38.9; 22.1 months, 17.8-26.4; 4.0 months, 3.6-4.4; p<0.001). As for timing of radiotherapy, SM+EBR (14.1 months, 12.7-15.5) was associated with inferior mOS than SM+DBR (19.4 months, 14.2-24.6) in EGFR/ALK-negative/unknown patients. No significant difference was found in EGFR/ALK-positive patients (28.3months, 19.1-37.5; 33.3months, 28.1-38.5). Patients in the EGFR/ALK-negative/unknown cohort treated with first-line pemetrexed with platinum (PP) (15.8 months, 14.0-17.6, p<0.001) had longer mOS than those received non-PP regimens (13.1 months, 11.6-14.6). However, no difference was observed among EGFR/ALK-positive patients who were treated with tyrosine kinase inhibitors (TKIs) (29.5 months, 21.1-37.9; p=0.140), PP (27.2 months, 21.6-32.8) and non-PP regimens (25.0 months, 16.0-34.0). Conclusions: Our study confirmed that the use of SM+BLT is associated with superior mOS than those treated with SM only and BLT only. SM+DBR might be a better radiotherapeutic strategy for this patient population. EGFR/ALK-negative/unknown patients showed a survival benefit with PP treatment.